Answer:
28, - 36
Explanation:
We are given a sequence of 1, - 3, 6, - 10, 15, -21, ..........
Now, the difference of 2nd and 1st term is (- 3 - 1) = - 4 = - 2²
Again, the difference of 3rd and 2nd term is [6 - ( -3)] = 9 = 3²
Now, the difference of 4th and 3rd term is [- 10 - 6] = - 16 = - 4²
Again, the difference of 5th and 4th term is [15 - ( -10)] = 25 = 5²
Now, the difference of 6th and 5th terms is [- 21 - 15] = - 36 = - 6²
Therefore, the difference of the terms are - 2², 3², - 4², 5², - 6², ..........
From this sequence, it is clear that the next two differences will be 7² i.e 49 and - 8² i.e. -64
Therefore, the next two terms of the original sequence will be (- 21 +49) = 28 and (28 - 64) = -36. (Answer)